2013
DOI: 10.1186/2050-7771-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-binding protein 1 as a tumor suppressor and a prognostic indicator of clinical outcome

Abstract: Selenium is a trace element that plays a critical role in physiological processes and cancer prevention, whose functions may be through its effects on selenium-containing proteins. Selenium-binding protein 1 (SBP1) is a member of an unusual class of selenium-containing proteins that may function as a tumor suppressor in multiple cancer types and whose levels have been shown to be lower in cancers as compared to corresponding normal tissues. This review is intended to summarize recent advances in gaining an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Furthermore, our in vitro and in vivo studies have also shown that increasing SBP1 expression in colorectal cancer cells attenuates cancer cell migration and tumor growth in nude mice [42]. Consistent with these findings, knockdown of SBP1 by small interfering RNA (siRNA) in the nontransformed human liver cells results in a substantial increase in cell proliferation index and migration capacity [27], suggesting that SBP1 acts as a tumor suppressor [43], which is further supported by the recent study that SBP1 negatively regulates HIF-1α expression and suppresses the malignant phenotype of prostate cancer cells [44].…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, our in vitro and in vivo studies have also shown that increasing SBP1 expression in colorectal cancer cells attenuates cancer cell migration and tumor growth in nude mice [42]. Consistent with these findings, knockdown of SBP1 by small interfering RNA (siRNA) in the nontransformed human liver cells results in a substantial increase in cell proliferation index and migration capacity [27], suggesting that SBP1 acts as a tumor suppressor [43], which is further supported by the recent study that SBP1 negatively regulates HIF-1α expression and suppresses the malignant phenotype of prostate cancer cells [44].…”
Section: Introductionsupporting
confidence: 64%
“…Compared with normal tissue, downregulation of SBP1 expression has been observed in several cancer types, such as gastric carcinoma, prostate, colon and ovarian cancer (Xia et al 2011;Giusti et al 2012;Yang and Diamond 2013). Previous data showed that SBP1 suppression promoted gastric cancer cell proliferation and cell migration, while SBP1 overexpression was associated with anti-cancer activities (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SBP1 was identified as a tumor suppressor and a prognostic indicator of clinical outcome (Yang and Diamond 2013). To understand the role of SBP1 in the inhibitory effect of selenium on gastric cancer cells, we measured the change of SBP1 expression in SGC7901 and N87 cells treated with 30 μM sodium selenite for 48 h. The results showed that sodium selenite elevated the expression level of SBP1 in both SGC7901 and N87 cells (Fig.…”
Section: Sodium Selenite Increases the Expression Level Of Sbp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Yang et al, selenium has three forms of protein categories, which are protein containing selenomethionine, protein containing selenocysteine, and peptide which bounded selenium such SELENBP1. 10 The assessment of selenium level in this study was done only by measuring SELENBP1 instead of measuring the total plasma of selenium level.…”
Section: Resultsmentioning
confidence: 99%